Effects of physical activity and sedentary behaviors on cardiovascular disease and the risk of all-cause mortality in overweight or obese middle-aged and older adults - Yongqiang Zhang; Xia Liu (Frontiers Media S.A., 2024)
AimThe aim of this study was to respectively explore the relationships between physical activity and sedentary behaviors and cardiovascular disease (CVD) and all-cause mortality risk in overweight/obese middle-aged and older patients, and also assess the interaction between physical activity and sedentary behaviors.MethodsData of middle-aged and older adults with body mass index (BMI) ≥25 kg/m2 were extracted from the National Health and Nutrition Examination Surveys (NHANES) database in 2007-2018 in this retrospective cohort study. Weighted univariate and multivariate logistic regression analyses were used to explore the associations between physical activity and sedentary behaviors and CVDs; weighted univariate and multivariate Cox regression analyses were used to explore the relationships between physical activity and sedentary behaviors with the risk of all-cause mortality. The interaction effect between physical activity and sedentary behaviors on CVD and all-cause mortality was also assessed. We further explored this interaction effect in subgroups of age and BMI. The evaluation indexes were odds ratios (ORs), hazard ratios (HRs), and 95% confidence intervals (CIs).ResultsAmong 13,699 eligible patients, 1,947 had CVD, and 1,560 died from all-cause mortality. After adjusting for covariates, patients who had high sedentary time seemed to have both high odds of CVD [OR = 1.24, 95% CI: (1.06-1.44)] and a high risk of all-cause mortality [HR = 1.20, 95% CI: (1.06-1.37)]. Furthermore, being insufficiently active was linked to high odds of CVD [OR = 1.24, 95% CI: (1.05-1.46)] as well as a high risk of all-cause mortality [HR = 1.32, 95% CI: (1.15-1.51)]. High sedentary time and being insufficiently active had an interaction effect on both high odds of CVD [OR = 1.44, 95% CI: (1.20-1.73)] and high risk of all-cause mortality [HR = 1.48, 95% CI: (1.24-1.76)]. Individuals of different ages with/without obesity need to focus on the potential CVD/mortality risk of high sedentary time and low physical activity (all P < 0.05).ConclusionReducing sedentary time combined with increasing physical activity may benefit health by reducing both the risk of CVD and all-cause mortality in overweight or obese middle-aged and older adults.